De la violence familiale à la violence institutionnelle. Le continuum des violences dans l’expérience des jeunes placés en protection de l’enfance - Isabelle Lacroix; Sarra Chaïeb; Pascale Dietrich‑Ragon; Isabelle Frechon (Populations Vulnérables, 2023)
For five years, several reports and testimonies from former foster children have alerted the public authorities to the violence children and young people may face in child protection institutions. However, their voices hardly get themselves heard. Based on a survey using questionnaires and interviews (the Longitudinal Survey on the leaving care of Young People from the Child, ELAP), this article analyses the continuum of violent situations – both before and during placement – that the young people we interviewed experienced. We will see that, in some cases, residential care and foster families are participating in producing or prolonging the violence that they should be ending.